2021
DOI: 10.1371/journal.pone.0247060
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 (ACE2) expression increases with age in patients requiring mechanical ventilation

Abstract: Mortality due to Covid-19 is highly associated with advanced age, owing in large part to severe lower respiratory tract infection. SARS-CoV-2 utilizes the host ACE2 receptor for infection. Whether ACE2 abundance in the lung contributes to age-associated vulnerability is currently unknown. We set out to characterize the RNA and protein expression profiles of ACE2 in aging human lung in the context of phenotypic parameters likely to affect lung physiology. Examining publicly available RNA sequencing data, we dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 77 publications
4
62
2
Order By: Relevance
“…There were inconsistent results regarding the ACE2 mRNA expression in alveolar macrophages reported by RNA‐seq analysis. Contrasted with the reports [ 14 , 15 , 16 ], the ACE2 mRNA expression in alveolar macrophages were indicated by other groups [ 5 , 11 , 13 ]. In agreement with these studies, our current studies have demonstrated ACE2 protein expression on alveolar, lipopolysaccharide (LPS)‐treated and other tissue macrophages [ 1 ].…”
Section: Literature Overview On Ace2 Expression On Human Lung Macrophagescontrasting
confidence: 95%
See 1 more Smart Citation
“…There were inconsistent results regarding the ACE2 mRNA expression in alveolar macrophages reported by RNA‐seq analysis. Contrasted with the reports [ 14 , 15 , 16 ], the ACE2 mRNA expression in alveolar macrophages were indicated by other groups [ 5 , 11 , 13 ]. In agreement with these studies, our current studies have demonstrated ACE2 protein expression on alveolar, lipopolysaccharide (LPS)‐treated and other tissue macrophages [ 1 ].…”
Section: Literature Overview On Ace2 Expression On Human Lung Macrophagescontrasting
confidence: 95%
“…The ACE2 expression on the surface of macrophages have been well established by studies such as ACE2 on alveolar macrophages [ 2 , 3 , 4 , 5 , 6 ], blood monocyte‐derived macrophages [ 7 , 8 , 9 ], and macrophages of atherosclerotic carotid arteries [ 10 ]. Specifically, the ACE2 protein expression on alveolar macrophages has been demonstrated by different studies with lung tissues from normal human and COVID‐19 patients (Table 1 ).…”
Section: Literature Overview On Ace2 Expression On Human Lung Macrophagesmentioning
confidence: 99%
“…In support of this notion, a humanized monoclonal antibody to GRP78 was recently shown to not only reduce cell surface ACE2 but to decrease SARS-CoV-2 entry and infection (Carlos et al, 2021 ). ACE2 expression is reported to increase with age in patients requiring mechanical ventilation (Baker et al, 2021 ), raising the additional possibility that mechanical ventilation may contribute to the observed increased GRP78 levels in pneumocytes via enhanced ACE2 in the autopsied COVID-19 lungs. However, age-related increase in ACE2 expression from mechanical ventilation alone cannot account for our observations because increased GRP78 scores in pneumocytes and macrophages were observed across all age groups with COVID-19, without a relationship to age.…”
Section: Discussionmentioning
confidence: 99%
“…Age is another risk factor for poorer prognosis in COVID-19 [ 53 ]. This age-associated vulnerability is probably due to increased expression of ACE2 with age accounting for higher mortality in elderly patients [ 64 ].…”
Section: Il-6: Predictor Of Disease Prognosis and Associated Risk Factors In Covid-19 Patientsmentioning
confidence: 99%